Facilitators and Barriers to Survey Participation by Physicians: A Call to Action for Researchers. (September 2013) - Klabunde, Carrie N.; Willis, Gordon B.; Casalino, Lawrence P.
Surveys of health care providers are a well-established tool for obtaining information about the organization and delivery of care as well as about provider knowledge and attitudes. However, declining response rates to provider surveys are a widely acknowledged concern. Although a number of studies have identified specific methods for increasing response rates in health care provider—and particularly physician—surveys, few have addressed the more fundamental question of what motivates or deters providers from survey participation. We briefly review theoretical perspectives concerning why providers choose to participate in surveys, and what is known about facilitators and barriers to participation. We then describe several research designs (i.e., focus groups, key informant interviews, diary and office workflow studies, surveying the surveyors, and follow-back studies of respondents/nonrespondents) for obtaining empirical data on facilitators and barriers to survey participation, particularly by physicians and medical groups. Researchers must begin to build an evidence base for understanding provider decisions concerning survey participation.